Performance of 6 routine coagulation assays on the new Roche Cobas t711 analyzer - Oostendorp, Marlies (Pract Lab Med, 2019)
OBJECTIVES: For new analyzers or tests, analytical evaluation is required before implementation in the clinical laboratory. We evaluated the novel Roche Cobas t711 analyzer with six newly developed coagulation assays: the activated partial thromboplastin time (aPTT), prothrombin time (PT), international normalized ratio (INR), fibrinogen, d-dimer and anti-Xa. The evaluation included imprecision experiments, method comparison with the currently used Stago STA-R Evolution, monitoring of unfractionated heparin (UFH) with aPTT, a fast centrifugation protocol to improve turn-around time, and determination of sample stability in whole blood and plasma. DESIGN AND METHODS: Imprecision and method comparison were assessed using commercial quality control samples and patient samples, respectively. For dose monitoring of UFH with the aPTT, samples from patients treated with UFH were used. Samples from healthy volunteers were collected for evaluation of the fast centrifugation protocol (5’ 2750×g) and for investigating sample stability over 6–8 h. RESULTS: Results for between-run precision were within the desirable specification. Method comparison showed an excellent agreement for fibrinogen, d-dimer and anti-Xa. For aPTT, PT and INR, a good correlation was found, but results were significantly lower on the t711 compared to the STA-R Evolution, which is caused by different coagulation activators. Results from the fast centrifugation protocol differed not significantly from the standard protocol (15’ 2500×g). Blood and plasma samples were stable at room temperature up to 6 and 8 h, respectively. CONCLUSIONS: The t711 coagulation analyzer with 6 novel tests is suitable for routine use in clinical laboratories.